Peroxynitrite Is a Key Mediator of the Cardioprotection Afforded by Ischemic Postconditioning In Vivo - Li, Jianhui (Public Library of Science, 2013)
Myocardial ischemic postconditioning (PosC) describes an acquired resistance to lethal ischemia-reperfusion (I/R) injury afforded by brief episodes of I/R applied immediately after the ischemic insult. Cardioprotection is conveyed by parallel signaling pathways converging to prevent mitochondria permeability transition. Recent observations indicated that PostC is associated with free radicals generation, including nitric oxide (NO(.)) and superoxide (O(2) (.-)), and that cardioprotection is abrogated by antioxidants. Since NO. And O(2) (. -) react to form peroxynitrite, we hypothesized that postC might trigger the formation of peroxyntrite to promote cardioprotection in vivo. Rats were exposed to 45 min of myocardial ischemia followed by 3h reperfusion. PostC (3 cycles of 30 seconds ischemia/30 seconds reperfusion) was applied at the end of index ischemia. In a subgroup of rats, the peroxynitrite decomposition catalyst 5,10,15,20-tetrakis(4-sulphonatophenyl) porphyrinato iron (FeTPPS) was given intravenously (10 mg/kg(-1)) 5 minutes before PostC. Myocardial nitrotyrosine was determined as an index of peroxynitrite formation. Infarct size (colorimetric technique and plasma creatine kinase-CK-levels) and left ventricle (LV) function (micro-tip pressure transducer), were determined. A significant generation of 3-nitrotyrosine was detected just after the PostC manoeuvre. PostC resulted in a marked reduction of infarct size, CK release and LV systolic dysfunction. Treatment with FeTPPS before PostC abrogated the beneficial effects of PostC on myocardial infarct size and LV function. Thus, peroxynitrite formed in the myocardium during PostC induces cardioprotective mechanisms improving both structural and functional integrity of the left ventricle exposed to ischemia and reperfusion in vivo.